Basic Workshop Personal Leadership For Student - Agus Fahmi; Hardiansyah Hardiansyah; Lukmanul Hakim; Lu'luin Najwa (Abdi Masyarakat, 2020)
Specifically in educational activities many schools learning centers and tertiary institutions stand in a variety of forms and fields of science. In the last decade there has been a decline in the value of leadership, especially for adolescents, in this case high school-age children who, when examined more deeply, found disciplinary attitudes, apathy, lack of social sense, and deteriorating educational achievement. The effect of this is the decreasing level of HDI (Human Development Index) of NTB. Based on data releases from BPS, it turns out that since 2010 NTB has been ranked 29th out of 33 provinces in Indonesia. Unfortunately since 2013 it has dropped back to 30th out of 34 provinces in Indonesia (BAPPEDA NTB: 2020). Therefore, it is important to provide knowledge and leadership training early on to teenagers through a Workshop with the theme Personal Leadership For Student in the hope that this training provides insight into the importance of having a leadership spirit that is supported by high motivation and confidence. Besides that, basic leadership training for students can also become routine and permanent schedule in schools so that the knowledge of leadership is not only an insight but also a soft skill values that are embedded in the character of young people who will lead in the future